Analysis of behaviour of composite elements with profiled steel sheet/Lenkiamųjų kompozitinių elementų, armuotų profiliuotais metalo lakštais, darbo analizė - Marčiukaitis, Gediminas; Valivonis, Juozas; Vaškevičius, Andrius (Journal of Civil Engineering and Management, 2001)
Joint action at the interface of concrete and profiled steel sheet layers of composite structures can be achieved in various ways. In most cases different types of roughness (embossments) are made inside sheet waves, which increase mechanical bond between concrete and sheets. Behaviour of such structures and particularly of the section at the interface of the layers is not fully investigated. The analysis performed has indicated that calculation methods proposed by various authors give different results. Theoretical and performed experimental investigations have shown that behaviour of interface zone is affected by concrete layer thickness, its deformation modulus, distribution of transverse and longitudinal deformations in concrete layers. On the basis of the theory of composite bars, a method for strength calculation of such structures was proposed; it gives opportunity to evaluate more accurately the behaviour of interface zone and other factors affecting the joint action of the structures under the load.Article in Lithuanian.First Published Online: 30 Jul 2012